m6A methylation modification and immune cell infiltration: implications for targeting the catalytic subunit m6A-METTL complex in gastrointestinal cancer immunotherapy - Peng, Chen; Xiong, Fen; Pu, Xi; Hu, Zhangmin; Yang, Yufei; Qiao, Xuehan; Jiang, Yuchun; Han, Miao; Wang, Deqiang; Li, Xiaoqin (Frontiers in Immunology, 2023)
N 6 -methyladenosine (m 6 A) methylation modification is a ubiquitous RNA modification involved in the regulation of various cellular processes, including regulation of RNA stability, metabolism, splicing and translation. Gastrointestinal (GI) cancers are some of the world's most common and fatal cancers. Emerging evidence has shown that m 6 A modification is dynamically regulated by a complex network of enzymes and that the catalytic subunit m 6 A-METTL complex (MAC)-METTL3/14, a core component of m 6 A methyltransferases, participates in the development and progression of GI cancers.Furthermore, it has been shown that METTL3/14 modulates immune cell infiltration in an m 6 A-dependent manner in TIME (Tumor immune microenvironment), thereby altering the response of cancer cells to ICIs (Immune checkpoint inhibitors).Immunotherapy has emerged as a promising approach for treating GI cancers. Moreover, targeting the expression of METTL3/14 and its downstream genes may improve patient response to immunotherapy. Therefore, understanding the role of MAC in the pathogenesis of GI cancers and its impact on immune cell infiltration may provide new insights into the development of effective therapeutic strategies for GI cancers.